Outcomes and prognostic factors in canine epitheliotropic and nonepitheliotropic cutaneous T‐cell lymphomas. (16th July 2021) - Azuma, Kazushi; Ohmi, Aki; Goto‐Koshino, Yuko; Tomiyasu, Hirotaka; Ohno, Koichi; Chambers, James K.; Uchida, Kazuyuki; Namba, Hiroyuki; Nagata, Masahiko; Nagamine, Eiji; Nibe, Kazumi; Irie, Mitsuhiro; et al.
Abstract: Canine cutaneous lymphoma is an uncommon lymphoma in dogs. Most canine cutaneous lymphoma cases have a T‐cell origin. Canine cutaneous T‐cell lymphoma (CTCL) is classified into epitheliotropic and nonepitheliotropic cutaneous lymphomas, and each type of lymphoma is subclassified into several histological subtypes. Limited information is available regarding the prognostic significance of clinical variables and histopathological subtypes in dogs with CTCL. This retrospective study aimed to investigate the influence of clinical variables and histopathological subtypes on the prognosis of dogs with CTCL. Forty‐six dogs diagnosed with CTCL by histopathological examination were included. Histopathological specimens were reexamined and classified into CTCL subtypes. The influence of the type of skin lesion, histopathological subtype, haematological examination results and treatment response on the overall survival time (OS) was examined. Thirty‐one dogs were diagnosed with epitheliotropic CTCL (mycosis fungoides in 28 dogs; pagetoid reticulosis in 3 dogs) and 15 dogs were diagnosed with nonepitheliotropic CTCL (anaplastic large T‐cell lymphoma in 6 dogs; peripheral T‐cell lymphoma, not otherwise specified, in 9 dogs). The OS of dogs diagnosed with epitheliotropic CTCL (141 days) was significantly shorter than that of dogs diagnosed with nonepitheliotropic CTCL (374 days). As clinical variables, the presence of neoplastic lymphocytes in peripheral blood, thrombocytopenia and initial chemotherapeutic response was related to prognosis. Our results demonstrated that histopathological subtype and several clinical variables were found to influence the prognosis of dogs with CTCL.